A Regimen of Taxol, Ifosfamide, and Platinum for Recurrent Advanced Squamous Cell Cancer of the Anal Canal. (25th May 2011) - Golub, Diana V.; Civelek, A. Cahid; Sharma, Vivek R.
Abstract : The typically recommended chemotherapy options in metastatic anal cancer generally yield partial remissions with limited benefit for the majority of patients. TIP is a regimen containing paclitaxel (Taxol), ifosfamide, and cisplatin that is known to have significant activity in patients with squamous cell cancers of the head and neck as well as in cervical cancer, both of which are malignancies strongly associated with oncogenic strains of human papilloma virus (HPV). Interestingly, squamous cell cancer of the anal canal shares an almost identical pathophysiology including causal association with HPV. Due to this, we chose to use the TIP regimen to treat patients with advanced anal cancer at our institution and report our findings on three such consecutive patients. All the patients tolerated the regimen well with manageable side effects and had excellent responses with complete resolution of PET activity after treatment. Our observations suggest that TIP is highly active for squamous cell cancer of the anal canal and warrants further study in the treatment of this disease.